The influence of cupric ions on shape of potentiodynamic curves obtained on 18 K gold - Rajčić-Vujasinović Mirjana; Trujić V.; Stević Zoran; Šaćirbegović S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The shape of potentiodynamic curves depends mainly on the composition of investigated alloys, but also on the electrolyte used in experiments. In this work investigation were performed for pure gold, and pure silver and copper as alloying metals, then for binary alloys Au-Ag and Au-Cu containing gold as in 18 k gold (i.e. 75 % Au) and Ag-Cu with mass ratio 1:1 and, finally, for three component 18 k gold. It was established a catalytic effect of cupric ions present in electrolyte on oxidation of gold and 18 k gold alloys.